Primary Intraosseous Cavernous Hemangioma of the Clivus: Case Report and Review of the Literature - Gologorsky, Yakov; Shrivastava, Raj K.; Panov, Fedor; Mascitelli, Justin; Signore, Anthony Del; Govindaraj, Satish; Smethurst, Mark; Bronster, David J. (Journal of Neurological Surgery Reports, 2013)
Primary intraosseous hemangiomas are benign, vascular malformations that account for approximately 1% of all primary bone neoplasms. These tumors are mostly found in vertebral bodies and are rarely seen in the calvarium, where they represent 0.2% of bony neoplasms. When found in the skull, they tend to present with vague symptoms and do not have the typical radiological findings suggestive of hemangiomas. Because of this, these tumors can be missed in many cases or may be misinterpreted as more ominous lesions like multiple myeloma or osteosarcoma. Involvement of the skull base is exceedingly rare, and presentation with cranial nerve unilateral polyneuropathies has not been reported. We report a patient case with review of recent pertinent literature.
Keywords: clivus; hemangioma; endoscopic transnasal surgery